Pedersen’s law and the rise of distinctive tone in Baltic and Slavic - Kortlandt, Frederik (Baltistica, 2018)
According to Pedersen’s law, the accent was retracted in Lith. acc.sg. dùkterį ‘daughter’ < *duktèrim, Greek θυγατέρα, and similar word forms. A reconsideration of the Balto-Slavic accent laws opened the way to explain the origin of Dybo’s “dominant” suffixes on the basis of Derksen’s end-stressed paradigms. Generalization of the Low tone of pretonic syllables to barytone forms of mobile accent paradigms gave rise to Olander’s “unaccented word-forms” with distinctive Low tone on the initial syllable. The rise of distinctive tone in Slavic originated from the extension of Pedersen’s law. In East Baltic, tonal contours came into being when the stress was retracted from prevocalic *‑ì‑ and final *‑à, yielding a rising tone that caused metatony in the preceding syllable. The rise of tonal contours in East Baltic has an interesting parallel in the development of the Franconian tone accents. Unlike Lithuanian and Latvian, Prussian had a quantitative but no tonal distinction in the vowel system.